Τεχνοοικονομική αξιολόγηση εγκατάστασης συστημάτων συμπαραγωγής και συγκεντρωτικού ηλιοθερμικού συστήματος για παραγωγή χρήσιμης θερμότητας για γαλακτοβιομηχανία - Παντελίδης, Ισίδωρος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Θερμότητας. Εργαστήριο Ατμοκινητήρων και Λεβήτων, 2016)
This thesis aims to make a technical and economical evaluation of alternative systems for the production of the process heat which is needed in a dairy plant. The type of systems that are investigated, are cogeneration (CHP-Combined Heat and Power) systems that produce both electricity and useful heat for the milk production. To require the process heat for the production, cogeneration systems with condensing steam turbine and back- pressure steam turbine are designed. Both of these systems have a steam boiler that consumes biomass. In addition, CHP systems with gas turbines and reciprocating internal combustion engines, which are powered by natural gas, are selected based on the heat output they provide. Finally, the installation of a concentrating solar power (CSP) system with parabolic troughs is examined in order to provide the dairy plant with a portion of process heat. All the alternative systems are financially evaluated by calculating the Net Present Value (NPV) and the Internal Rate of Return (IRR). Additionally, a sensitivity analysis is carried out in order to find out the crucial factors of each case study. From the financial analysis, we conclude which type of system is a suitable and profitable investment for the dairy plant.